Assessing the effective communication of world heritage brand of protected areas: a case of Kinabalu Park / Christy Bidder, Boyd Sun Fatt and Spencer Hedley Mogindol - Bidder, Christy Bidder; Sun Fatt, Boyd; Mogindol, Spencer Hedley (Universiti Teknologi MARA, Perak, 2022)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) designates World Heritage Sites (WHS) of outstanding universal value to cultural or natural heritage. The highest recognition or honor that the site/property can receive is the designation of a site/ property as a UNESCO WHS. This can play an imperative role in the long-term sustainability of protected areas through developing greater visitor and community understanding, appreciation of the WHS concept and acknowledging the outstanding universal values of individual WHS properties. However, the role that WHS brand plays can only materialize if the communication of the brand is effective. Drawing on this background, the current research assessed the effective communication of WHS brand of a UNESCO WHS in Malaysia, namely Kinabalu Park (KP). Specifically, it aimed to achieve the following three objectives: 1) to examine visitors' awareness of KP's WHS listing; 2) to examine the extent to which KP's WHS listing has impacted the park's visitor numbers, and 3) to analyze visitors' perceived meaning attached to KP's WHS listing. Quantitative data were collected both onsite and online and analyzed using descriptive statistics. Primary results indicated an ineffective communication of KP's WHS brand, as evidenced by the inability of visitors to recognize the brand or what it embodied, as well as their assignment of a greater tourism meaning/value, instead of conservation, to KP's WHS designation. It was also discovered that there was an increase in the park's visitor numbers post-designation, though it was arguable that the increase could be attributable to other intervening factors. The results emphasized the need for KP's management to properly follow the WHS brand guidelines stipulated by the World Heritage Committee and create a better interpretation of KP's WHS designation for a more effective communication of the brand.